Implications of Black Coffee Twig Borer on cocoa in Uganda - Kagezi, G.H.; Kucel, P.; Egonyu, J.P.; Ahumuza, G.; Nakibuule, L.; Kobusinge, J.; Wagoire, W.W. (African Journals Online (AJOL), 2014)
Cocoa (Theobroma cacao L.) is one of Uganda’s major cash crops. It is grown by 15,000-18,000 smallholder households on an estimated 20,000 hectares. Cocoa contributes about US$65 million annually to the country’s foreign exchange earnings. On account of its perennial nature and robust vegetative growth, cocoa harbors a wide range of insect pests which affect its production. Here, we report for the first time an outbreak of the Black Coffee Twig Borer (BCTB), Xylosandrus compactus (Eichhoff), a new pest on cocoa in Uganda. To determine its spread and impact, we surveyed 20 households in Bundibugyo, Kibaale and Hoima districts in January 2014. On each field, 10 cocoa trees were examined for BCTB infestation along a transect. Overall, more than half of the cocoa plantations, 13% of trees and 3.8% of primary branches were infested. At district level, Kibaale had the highest proportions of infested fields (100%), trees (30%) and primary branches (8.5%). The seriousness of BCTB prevalence is likely to complicate the current BCTB spray programme on coffee in the country.